Carbon polygons: Greenhouse gas monitoring methods - Eskiev Muslim; Jandarova Louise; Akhmieva Roza (BIO Web of Conferences, 2023)
The study of carbon polygons and their role in greenhouse gas dynamics is of paramount importance in the context of climate change and global environmental concerns. Carbon polygons, also known as peat plateaus or peat polygons, represent unique ecosystems found in northern regions, which play a significant role in the global carbon cycle. These landscapes consist of a mosaic of waterlogged polygon centers and elevated rims, characterized by diverse vegetation and complex hydrological processes. One of the key concerns regarding carbon polygons is their potential to release greenhouse gases, primarily methane and carbon dioxide, into the atmosphere. As global temperatures rise and permafrost thaws in northern areas, these ecosystems become critical focal points for scientific research and monitoring.